Efficacy and safety of metformin or oral contraceptives, or both in polycystic ovary syndrome - Yang YM; Choi EJ (Dove Medical Press, 2015)
Young-Mo Yang, Eun Joo Choi College of Pharmacy, Chosun University, Gwangju, South Korea Background: Polycystic ovary syndrome (PCOS) is an endocrinopathy that affects approximately 10% of reproductive-aged women throughout their lives. Women with PCOS present with heterogeneous symptoms including ovulatory dysfunction, hyperandrogenism, and polycystic ovaries. Therefore, lifelong individualized management should be considered. Pharmacological agents commonly used to manage the symptoms are metformin and oral contraceptive pills. Although these medications have been beneficial in treating PCOS symptoms, their efficacy and safety are still not entirely elucidated. This study aimed to report the efficacy and safety of metformin, oral contraceptives, or their combination in the treatment of PCOS and to define their specific individual roles.Methods: A literature search of original studies published in PubMed and Scopus was conducted to identify studies comparing metformin with oral contraceptives or evaluating the combination of both in PCOS.  Results: Eight clinical trials involving 313 patients were examined in the review. The intervention dosage of metformin ranged from 1,000 to 2,000 mg/d and that of oral contraceptives was ethinylestradiol 35 µg and cyproterone acetate 2 mg. Lower body mass index was observed with regimens including metformin, but increased body mass index was observed in monotherapy with oral contraceptives. Administration of metformin or oral contraceptives, especially as monotherapy, had a negative effect on lipid profiles. In addition, there are still uncertainties surrounding the effects of metformin or oral contraceptives in the management of insulin level, although they improved total testosterone and sex hormone-binding globulin levels. In the included studies, significant side effects due to metformin or oral contraceptives were not reported.  Conclusion: The clinical trials suggest that metformin or oral contraceptives are at least patient convenient, efficacious, and safe for the treatment of PCOS. However, well-designed, prospective, long-term, large-scale, randomized clinical trials are necessary to elucidate the efficacy and safety of metformin, oral contraceptives, or both in the treatment of PCOS, and to elucidate their individual roles in the treatment of this condition. Keywords: polycystic ovary syndrome, metformin, oral contraceptive pill, ovulatory dysfunction, hyperandrogenism, efficacy, safety